Enhancing Cellular Infiltration on Fluffy Polyaniline-Based Electrospun Nanofibers - Daraeinejad, Zohreh; Shabani, Iman (Frontiers in Bioengineering and Biotechnology, 2021)
Despite the unique properties of polyaniline (PANI), the processability of this smart polymer is associated with challenges. Particularly, it is very difficult to prepare PANI nanofibers due to poor solubility, high charge density, and rigid backbone. The most common approach for solving this problem is blending PANI with a carrier polymer. Furthermore, the major limitations of nanofibers for tissue engineering applications are their low porosity and two-dimensional (2D) structure. In this study, conductive nanofibers were fabricated through electrospinning of PANI/poly(ether sulfone) (PES) with different solvents including dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), and hexafluoroisopropanol (HFIP). The effect of solvent, carrier polymer (PES), and PANI content on formation of 3D conductive nanofibers with appropriate porosity were investigated. It was shown that a solvent with suitable properties should be selected in such a way that the composite nanofibers can be electrospun at the lowest concentration of PES. In this way, the ratio of PANI increased in the scaffold, the electrical conductivity of nanofibers enhanced, and the flat 2D structure of scaffold changed to a fluffy 3D structure. Among the three studied solvents, HFIP with the lowest boiling point and the lowest surface tension was the best solvent for the fabrication of PANI/PES nanofibers. PES could be electrospun at a concentration of 9% w/w/ in HFIP, while the optimum percentage of PES in DMSO and NMP was above 23% w/w to produce uniform nanofibers. 3D nanofibrous scaffold obtained from 0.5% PANI/9% PES/HFIP solution with electrical conductivity of 3.7×10-5 S/Cm and porosity of 92.81 ± 1.23%. Cell infiltration into the 3D nanofibers with low packing density improved compared to densely packed 2D nanofibers.